Análisis de las situaciones de violencia ocurridas o detectadas en el sistema educativo de Ecuador. Una etnografía escolar con conclusiones y recomendaciones (Investigaciones) - Martínez Pérez, Ana (2022)
The main objective of the research that allows elaborating this theoretical reflection is to know the processes of violence towards children and adolescents that occurred or detected in the Ecuadorian educational context, carrying out a school ethnography, to determine a series of recommendations to reduce their incidence to the regional and global level. The methodology used focused on using qualitative research techniques since the Ministry of education had quantitative data that deserved to be correlated to obtain significantly and not only representative results. Therefore, analyzing the previous statistical data and the qualitative results obtained from a school ethnography (participant observation, interviews, discussion groups, documentary) allows a series of conclusions and recommendations to influence the public policies that prevent violence in the education system.